Leadership Styles in Bulgarian Municipalities - Traykova, Loreta (Research Papers, 2024)
The purpose of the article is to explore the leadership styles in Bulgarian municipalities. It argues that in their management the mayor rarely applies only one style, but the most effective and preferred is the leadership style which is oriented at fulfilling the commitments made to the residents of the relevant municipality/district and the employees in the administration, because in the governance at the local level, the close, daily contact of the leader with the followers (of the mayor with the voters and employees) is of particular importance.Part of the results of an author's study of mayors in municipalities and districts in the Republic of Bulgaria are presented. The methods used to analyse the collected data are descriptive statistics, arithmetic mean calculation and correlation analysis.The study reveals that the most common leadership style adopted by the Bulgarian mayors is the transformational one.In further work on the topic, an association between the applied leadership style and the financial-economic condition of the municipality/region can be investigated as well as qualitative methods will also be included – in-depth interviews, case studies, with the aim of examining the specific features of each leadership style and linking them to the broader context.
Keywords: Mayors; Leadership styles; Municipalities; Leadership; Bulgaria